Comparative Effectiveness of Interactive Panel Board and Chalkboard Teaching Aids among Second-year MBBS Students: A Quasi-experimental Study - Krishna Singh; Rahul Vaish; Dheeraj Kumar Mulchandani; Ashish Kumar Dixit (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: The Competency-Based Medical Education (CBME) stresses practicality, reasoning, and engagement. Many consider pharmacology challenging, and hence, there is a need for an efficient way to teach the course. There is a paucity of literature comparing the effectiveness of interactive smart panel boards and chalkboard teaching based on objective parameters in India. Aim: To evaluate and to compare interactive smart panel board and chalkboard teaching in undergraduate pharmacology. Materials and Methods: The present quasi-experiment was performed on 103 second-year Bachelor of Medicine and Bachelor of Surgery (MBBS) students in the Department of Pharmacology, Hind Institute of Medical Sciences, Barabanki, Uttar Pradesh, India, from February 2025 to March 2025. Six topics related to the Central Nervous System (CNS) were covered by either the interactive panel board method (3 topics) or the chalkboard (3 topics) in random order. Change in knowledge was evaluated using pre-test and post-test Multiple-Choice Questions (MCQs). Perception was measured by a 17-item Likert scale questionnaire. Paired and independent sample Student’s t-test was used to analyse data. Statistical significance was set at p